A novel EBSD‐based finite‐element wave propagation model for investigating seismic anisotropy: Application to Finero Peridotite, Ivrea‐Verbano Zone, Northern Italy. Issue 20 (27th October 2014) - Zhong, Xin; Frehner, Marcel; Kunze, Karsten; Zappone, Alba
Abstract A novel electron backscatter diffraction (EBSD) ‐based finite‐element (FE) wave propagation simulation is presented and applied to investigate seismic anisotropy of peridotite samples. The FE model simulates the dynamic propagation of seismic waves along any chosen direction through representative 2D EBSD sections. The numerical model allows separation of the effects of crystallographic preferred orientation (CPO) and shape preferred orientation (SPO). The obtained seismic velocities with respect to specimen orientation are compared with Voigt‐Reuss‐Hill estimates and with laboratory measurements. The results of these three independent methods testify that CPO is the dominant factor controlling seismic anisotropy. Fracture fillings and minor minerals like hornblende only influence the seismic anisotropy if their volume proportion is sufficiently large (up to 23%). The SPO influence is minor compared to the other factors. The presented FE model is discussed with regard to its potential in simulating seismic wave propagation using EBSD data representing natural rock petrofabrics.